Cytokines IL-17 and IL-22 in the host response to infection - Valeri, Maria (Pathog Dis, 2016)
Cytokines IL-17 and IL-22 play pivotal roles in host defense against microbes and in the development of chronic inflammatory diseases. These cytokines are produced by cells that are often located in epithelial barriers, including subsets of T cells and innate lymphoid cells. In general, IL-17 and IL-22 can be characterized as important cytokines in the rapid response to infectious agents, both by recruiting neutrophils and by inducing the production of antimicrobial peptides. Although each cytokine induces an innate immune response in epithelial cells, their functional spectra are generally distinct: IL-17 mainly induces an inflammatory tissue response and is involved in the pathogenesis of several autoimmune diseases, whereas IL-22 is largely protective and regenerative. In this review, we compare IL-17 and IL-22, describing overlaps and differences in their cellular sources as well as their regulation, signaling, biological functions and roles during disease, with a focus on the contribution of these cytokines to the gut mucosal barrier during bacterial infection.